2020
DOI: 10.3390/cancers12103022
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Ion Radiobiology

Abstract: Radiotherapy using accelerated charged particles is rapidly growing worldwide. About 85% of the cancer patients receiving particle therapy are irradiated with protons, which have physical advantages compared to X-rays but a similar biological response. In addition to the ballistic advantages, heavy ions present specific radiobiological features that can make them attractive for treating radioresistant, hypoxic tumors. An ideal heavy ion should have lower toxicity in the entrance channel (normal tissue) and be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
154
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 325 publications
4
154
0
Order By: Relevance
“…In addition, 12 C ions' energy deposition patterns result in more complex DNA lesions that are more difficult to repair, so combined treatment with DNA repair inhibitors may hold greater promise. National Institute of Radiological Sciences (NIRS) in Chiba, Japan leads in treating patients with carbon ions and it has treated more than 13,000 patients since 1994 [55]. Relying on their experience with fast neutrons, the NIRS team determined the RBE for their passive system across a spread-out Bragg Peak by using either Chinese hamster ovary cells or, ultimately, human salivary gland (HSG) cells in their microdosimetric kinetic model (MKM) [56].…”
Section: Proton Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 12 C ions' energy deposition patterns result in more complex DNA lesions that are more difficult to repair, so combined treatment with DNA repair inhibitors may hold greater promise. National Institute of Radiological Sciences (NIRS) in Chiba, Japan leads in treating patients with carbon ions and it has treated more than 13,000 patients since 1994 [55]. Relying on their experience with fast neutrons, the NIRS team determined the RBE for their passive system across a spread-out Bragg Peak by using either Chinese hamster ovary cells or, ultimately, human salivary gland (HSG) cells in their microdosimetric kinetic model (MKM) [56].…”
Section: Proton Therapymentioning
confidence: 99%
“…Even though 13,000 individuals have been treated with 12 C ions, no randomized phase III clinical trials have been completed to date. Nonetheless, an abundance of evidence from phase II studies suggests that CIRT achieves excellent treatment responses with favorable safety profiles, even though treatment regimens were developed empirically [55]. For instance, treating skull base chordomas and chordosarcomas with CIRT achieves excellent tumor control and overall survival with a low level of toxicity [58][59][60].…”
Section: Proton Therapymentioning
confidence: 99%
“…Moreover, there are some indications that heavy ions cans potentiate the immune response in a more effective way than photons, or even proton beams [ 5 ]. This might result in a highly effective synergic effect with the potential immune activation in spatially fractionated radiation therapy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of their increased linear energy transfer, heavy ions, like Neon, Silicon, or Argon, provide a reduced oxygen enhancement effect [ 4 ]. Linked to that, evidence exists that (very) heavy ions are more advantageous than X-rays (conventional radiation therapy) for the treatment of those hypoxic and radioresistant tumours [ 5 , 6 ]. Pioneering radiobiological evaluations showed that resistant cells of hypoxic tumours could be effectively killed with heavy ions beams [ 6 ], such as Silicon and Argon.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to enhance the efficacy of RT for osteosarcoma is the use of high linear energy transfer carbon-ion RT (CIRT) that causes more double-strand breaks in DNA than photon or proton therapy, with great dose conformity [22][23][24]. It has been shown as a promising method of overcoming radioresistance of osteosarcoma cells [25].…”
Section: Discussionmentioning
confidence: 99%